Waste to energy concept: A detailed experimental investigation of engine behaviors fueled by waste pyrolysis oil with nano-sized particles and Oxyhydrogen - El-Shafay, Ahmed. S.; Fareed, Aisha F.; Gad, M. S.; Agbulut, Umit (SPRINGER, 2025)
In the present research, the waste tires are converted into pyrolysis oil to obtain an alternative fuel for internal combustion engines. Then, the pyrolysis oil is volumetrically blended with pure diesel fuel at 20%. After this step, to enhance the fuel properties, nanoparticle-sized aluminum oxide (Al2O3) was separately incorporated into the test mixture at concentrations of 25, 50, and 100 ppm. Oxyhydrogen gas was yielded by water electrolysis using an alkaline electrolyzer at 0.5 LPM. Tests were run at 3000 rpm rated speed and range of engine brake power. In the results, it is noticed that test blends of Al2O3 (TO20A25 + HHO, TO20A50 + HHO, and TO20A100 + HHO) in pyrolysis oil enhanced thermal efficiencies by 8.5%, 11%, and 15.25%, while specific fuel consumptions were reduced by 8.7%, 10.8%, and 15%, respectively, compared to TO20. Furthermore, the incorporation of 25, 50, and 100 mg/L of nano-alumina into pyrolysis oil with HHO results in significant reductions in CO emissions of 16%, 19%, and 23% as compared to TO20. The research indicated substantial reductions in HC emissions of 26%, 32%, and 36%, alongside marked decreases in smoke values of 25%, 30%, and 35% for TO20A25 + HHO, TO20A50 + HHO, and TO20A100 + HHO, respectively. Furthermore, NOx concentrations noteworthy reduced by 20%, 23%, and 27% with the introduction of HHO to oil mixtures with 25, 50, and 100 ppm of nanoparticles, respectively. The combination of oil with nano-additions and HHO support resulted in enhanced cylinder pressure and heat release rate. The incorporation of pyrolysis oil derived from waste tires, augmented with 100 ppm aluminum oxide and HHO, has a significant potential to reduce exhaust emissions, enhance combustion efficiency, as well as improve engine performance, and contribute to solid waste management.
Keywords: Waste to energy; Pyrolysis oil; Nanofuels; HHO; Engine performance; Combustion; EMISSION CHARACTERISTICS; TYRE PYROLYSIS; BIO-OIL; PERFORMANCE; BIODIESEL; ALCOHOL; BLENDS; Thermodynamics; Chemistry